Effect of oxygen plasma treatment on the electrochemical properties of Prussian blue electrodes for transparent electrochromic devices - Kim, A-Young; Park, Ji Hun; Byun, Dongjin; Lee, Joong Kee (ELSEVIER SCIENCE SA, 2013)
The effect of oxygen plasma on the electrochromic characteristics of electrochromic devices that utilize Prussian blue electrodes is investigated. Prussian blue working electrodes were electrodeposited on fluorine-doped tin oxide films that were grown on glass substrates by electron cyclotron resonance-metal organic chemical vapor deposition. An indiumtin oxide coated glass was employed as the counter electrode that served as an ion storage layer. The goal of the oxygen plasma treatment is to increase the oxygen functional groups on the surface of the Prussian blue electrode leading to the enhancement of the oxidation reaction and eventually the increase in coloration efficiency. Improvement of electrochromic properties, such as optical density and response time, was also observed following plasma treatment. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: OXIDE COMPOSITE FILMS; PHOTOELECTRON-SPECTROSCOPY; AIR; INTERFACE; TITANIUM; NITROGEN; PET